Technical design report for the CODEX-β demonstrator - Aielli, Giulio; Alimena, Juliette; Balcarcel-Salazar, Saul; Beacham, James; Haim, Eli Ben; Burucs, András Barnabás; Cardarelli, Roberto; Charles, Matthew J.; Vidal, Xabier Cid; Roeck, Albert De; Dey, Biplab; Dobrescu, Silviu; et al. (Journal of instrumentation, 2025)
The CODEX- β apparatus is a demonstrator for the proposed future CODEX-b experiment, a long-lived-particle detector foreseen for operation at IP8 during HL-LHC data-taking. The demonstrator project, intended to collect data in 2025, is described, with a particular focus on the design, construction, and installation of the new apparatus.